Misrepresenting Health Conditions Through Fabrication and Exaggeration: An Adaptation and Replication of the False Alarm Effect. Issue 5 (4th May 2018) - Thompson, Charee M.; Lin, Hengjun; Parsloe, Sarah
ABSTRACT: This article reports on a series of studies of the false alarm effect (FAE), suggesting that individuals' perceptions that relational partners are fabricating and exaggerating their health conditions are negatively associated with perceptions of health condition credibility, which in turn are associated with decreases in individuals' protective behaviors and attitudes. In Study One ( N = 216), we took a mixed-methods approach to test an initial model predicting that health condition credibility mediates associations between individuals' perceptions that partners are fabricating and exaggerating and the extent to which individuals provide support, seek information about the condition, feel efficacious in their ability to assist partners, and believe that the condition is serious. We also analyzed open-ended responses to parse the source(s) of credibility lost when individuals believe partners are fabricating and exaggerating their health conditions. We found that they express doubt not only about the credibility of the health condition itself, but also about their partner's credibility in terms of trustworthiness. We then refined our conceptual model to account for these two sources of credibility and tested it with a path model in a second study utilizing a nationally representative sample ( N = 508). Results supported our hypotheses. We discuss the implications of this research for how people present themselves as ill in personal relationships, and what happens when these presentations are unconvincing.